Intrinsic functional connectivity of the periaqueductal gray, a resting fMRI study - Kong, Jian (2010)
The periaqueductal gray (PAG) is known to play a crucial role in pain modulation and has shown a strong interaction with anterior cingulate cortex in previous functional imaging studies. We investigated the intrinsic functional connectivity of PAG using resting fMRI data from 100 subjects. The results showed that PAG is functionally connected to ACC (rostral and pregenual ACC) and also rostral ventromedial medulla (RVM), forming a core ACC-PAG-RVM network for pain modulation even no pain stimulus is applied. The comparison between genders showed that for the contrast of female minus male, significant difference was observed at mid-cingulate cortex; for the contrast of male minus female, significant differences were observed at left medial orbital prefrontal cortex, and uncus; right insula /operculum and prefrontal cortex. We believe eluciation of this Intrinsic PAG network duing the resting state will enhance our physiological and pathological understanding of the development and maintenance of chronic pain states.